HISTORICOSOPHIC DOMINANTS IN THE NOVELS BY V. SHAROV (Proceedings of Southern Federal University. Philology, 2013)
Sorokina T.E.Keywords: art historiosophy, historiosophic dominants, mythology of reality, religious subtext.The article studies the philosophy of history as a literary reality in the novels by Vladimir Sharov. His novels recreate the events of the Russian Revolution and Soviet Times in the perspective of eschatology.